Changes in forest habitat types in the vicinity of Sulejów Reservoir, Pilica River, Poland - Będkowski , Krzysztof; Jaskulski , Marcin (Acta Geographica Lodziensia, 2024)
Water reservoirs have a significant impact on the environment, mainly through their impact on groundwater levels. Water is an important soil-forming factor, and its availability and soil fertility determine the development of forest habitats typical of given conditions. However, long-term changes in water regimes result in habitat changes. We examined changes in forest habitats that occurred in the vicinity of the Sulejów Reservoir in the zone up to 750 m from the bank and with a difference in height from the water level of up to +5 m. Detailed research covered a total area of 710 ha. We used data from periodic forest inventories. We found changes in forest habitats, mainly involving an increase in their humidity. Fertility also increased in part of the area, which we attribute to moisture improving the availability of elements important for the development of vegetation. Habitat changes occur mainly in the north-western parts of the study area. The penetration of water into the surroundings of the reservoir is most pronounced in the areas of several tributaries, because when the level of damming is high, their role changes – instead of supplying water to the reservoir, they cause its outflow.